COLOR INDICATOR FILM FROM BUTTERFLY PEA (Clitoria ternatea L.) AS SMART PACKAGING IN BROILER CHICKEN MEAT - Hermawan Seftiono; Della Ayu Pramesti; Inanpi Hidayati Sumiasih (Hasanuddin University, 2021)
Broiler chicken is one of the poultry products that are very susceptible to damage due to exposure to microbes, temperature, and light. In these conditions, indicators are needed to play a role in informing related changes in the product quality. The butterfly pea can be used as an indicator because it contains anthocyanin which can change color due to the influence of pH. The objective of this study was to obtain the best indicator film formulation and to determine the film response in detecting the level of damage of the chicken meat through parameters of color change, thickness, pH, TPC, and TVBN. The methods in this research were the extraction of butterfly pea, making indicator films, and applying the film to chicken meat, and physical and chemical analysis of the product. Anthocyanin was applied to the indicator film with levels of PVA and chitosan 20:80 with the addition of 5 mL of dye. The change in color of the indicator could be seen at the 24-hour mark, which was a yellowish-green color. The pH value of broiler chicken meat had entered the post-rigor stage at 24 hours with a pH value of 6.595±0.049. The TVBN regression value showed that broiler chicken meat was not safe for consumption after being stored for 4 hours and 23 minutes of 40 mgN/100 g. The TPC test that has been performed in chicken meat showed that the chicken meat was not safe for consumption in storage between 0 to 8 hours at 5.598±0.068 log CFU/g to 8.322± 0.053 log CFU/g. Keywords: anthocyanin, discoloration, pH indicator, TVBN